Graphene oxide deposition on neodymium doped zinc borotellurite glass surface: Optical and polarizability study for future fiber optics - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2021)
Graphene oxide deposition on neodymium doped zinc borotellurite glass surface: Optical and polarizability study for future fiber optics by Muhammad Noorazlan Abd Azis